Significant dysregulation of lipid metabolism in patients with papillary thyroid carcinoma after thyroidectomy - Zhou, Liang; Li, Shuo; Wu, Yuqi; Chen, Qianming; Hu, Xiaotong; Jiang, Junchang; Shi, Yaoyao; Shen, Dan; Xie, Lei (Frontiers in Endocrinology, 2023)
Thyroidectomy and thyrotropin suppressive therapy is the widely used surgical treatment for papillary thyroid carcinoma (PTC) patients. However, systematic metabolic changes of postoperative PTC patients were rarely reported. Here, untargeted metabolomic detection of cohorts from PTC before (t0) and 1-month-after (t1) thyroidectomy, were performed to characterize circulating metabolic signatures after surgical treatment. Our results showed PTC patients exhibited lower thyroid stimulating hormone degree, higher total thyroxine, and significant lipid-related metabolic alternations after thyroidectomy, which included 97 upregulations (including 93 lipids) and 5 downregulations (including 2 lipids and 3 nucleotides). Enrichment of metabolic pathways mainly included biosynthesis of fatty acids, purine metabolism, and linoleic acid metabolism. We also demonstrated that differential surgical approaches (hemi-and total thyroidectomy) and post-operative complication phenotypes (insomnia, fatigue), might lead to characteristic metabolic signatures. This study revealed dynamic changes of metabolite characteristics of PTC patients after surgical treatment, This is a provisional file, not the final typeset article which were associated with clinical thyroid function parameters, surgical approaches, and complication occurrence. It enlightened us to pay more attention on the post-operative metabolic dysregulation of PTC patients and their long-term qualities of life, so as to provide cautious clinical decisions on surgical choices, treatments, and follow-up details.